OPTIMASI FORMULA TABLET DISPERSIBLE EKSTRAK DAUN JAMBU BIJI DENGAN KOMBINASI BAHAN PENGHANCUR CROSCARMELLOSE SODIUM DAN SODIUM STARCH GLYCOLATE - Aditya Novera Rachmawati; Wahyono Wahyono; T. Nanda Saifullah Sulaiman (Majalah Obat Tradisional, 2015)
The efficacy and safety of guajava leaf (Psidium guajava L.) extract as antidiarrheal has been tested through pra-clinical and clinical studies. Now dosage form of guajava leaves extract as antidiarrheal has limitation for childrens because it is difficult oto be swallowed, it has high disintegration time and unpleasent smell and flavor so it needs an acceptable dosage formulation for childrens. The aim of this research is to optimize formula dispersible tablets with combination disintegrants of croscarmellose sodium (CCS) and sodium starch glycolate (SSG). Dispersible tablets were produced by dry granulation with five formulas, i.e. formula I (100% CCS), II(75%:25%), III(50%:50%), IV (25%:75%) and V (100% SSG). Standarization of the extract used organoleptic parameters, loss on drying value and thin layer chromatography (TLC). The dispersible tablets were tested for weight uniformity, friability, hardness, disintegration time, dispersion time, wetting time and TLC. Data were analyzed using sofware Design Expert® versi 7.1.4.0 to determine the optimum formula. The result showed that the different compositions of CCS-SSG influence the physical charasteristics of dispersible tablets. The higher of SSG content will increase the hardness, the disintegration time, the dispersion time and the wetting time. The optimum formula was the formula with combination of 71% CCS and 29% SSG.